Opinion on Service Performance (SERVPERF) of Online Shopping Delivery in Nepal - Vaidya, Rashesh; Yogi, Suraj (ARRUS Journal of Social Sciences and Humanities, 2021)
Nepalese online shopping companies have not been maintaining the proper warehouse facilities but have been getting goods from the third party, even for the delivery service. Hence, if the delivery service provider makes an error in due process of delivering goods, indirectly, the image and goodwill of the online shopping company seem to be hampered. The paper found the assurance from the delivery personnel is seen as very poor as per the opinion of the Nepalese online shoppers while there was no issue on the responsiveness from the side of the delivery personnel. Similarly, the correlation coefficient analysis found that every element of the SERVPERF is correlated with customer satisfaction regarding the quality of online delivery service. Hence, customer satisfaction is hampered if the delivery personnel ignores any one of the elements of SERVPERF.